Manual on collective bargaining and dispute resolution in the public service (International Labour Office, 2011)
Aims to identify approaches and practices around the world which have enabled unions and public sector employers to engage in negotiations regarding wages and conditions of work on a fair footing and with minimal disruption to public services.